Իրաքի, Լիբիայի, Սիրիայի դեմ տեղեկատվական պատերազմների համեմատական վերլուծություն - Նազարյան, Հայկ (YSU Journal of International Affairs, 2015)
It is known that military actions are preceded or at least followed by information and psychological activities. They are aimed to pressure the addressee and to influence it. Such actions could lead to the cleavage of the main forces of the counterparts, their demoralization. Nowadays the rapid growth of modern communication and information technologies enables the state which “sets the rules” of the game to present its counterpart countries as discredited, representing a threat, non-democratic and so forth. For these reasons, it is more than urgent to explore information warfares and the resemblances between the main principles of those warfares that were conducted against Iraq, Libya and Syria.
Keywords: information warfare, comparative analysis, mass media, public opinion, propaganda, chemical weapon